Implikasi Budaya Organisasi Terhadap Disiplin Kerja Karyawan Pada PT Kereta Api Indonesia (Persero) Daerah Operasi 1 Jakarta - Lestari, Nurlaela Eva Puji (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2022)
Abstract-Organizational Culture has an important role in efforts to achieve organizational goals and for organization have employee high discipline that is very desired by organization. This research uses quantitative descriptive with questionnaires research instrument with 35 respondens. The sampling that used are saturation sampling using likert scale, the calculate methods the use are test of correlation coefficient, determination coefficient and regression equation. Data processing uses the help of the Statistical Package For Social Sciences (SPSS) computer application program. Multiple regression analysis techniue was used to analyze this research. The results show that there is a positive influence between organizational culture variables on employee work dicipline, with the coefficient of determination of organizational culture on work discipline with the remaining 37.1% can be explained by other factors such as work environment, compensation, motivation and others. This implies that companies must focus on improving organizational culture to be able to improve employee work discipline.Keywords: Organizational Culture, Work Discipline